Analysis of contractor capacity level in following E-tender in Gianyar District - Suasira, I Wayan; Santiana, I Made Anom; Wibawa, I Gede Sastra; Yasa, I Made Tapa; Yuliadewi, Ni Putu Ary (International research journal of engineering, IT and scientific research, 2023)
The implementation of government procurement of goods/services in the Gianyar Regency is carried out electronically by E-Tendering. In practice, the participation and bid value of bidders tends to decrease both during conventional auctions and electronic auctions. This study aims to determine the level of contractors’ ability to participate in e-tenders, factors that affect participation or contracts not to participate in e-tenders, and what deficiencies exist in the implementation of e-tenders in Gianyar Regency. The sample used in this study were 73 contractor companies in this Regency in the analysis of the contractor’s ability level, and 43 companies in the factor and deficiency analysis where this number used the sampling method using simple random sampling technique with purposive sampling and data collection using observation from GAPENSI Gianyar Regency and questionnaires. Data analysis was carried out by descriptive analysis. From the results of the analysis of contractors, the dominant qualification is K1. Therefore, the contractor’s ability to participate in e-tenders is the most dominant in projects valued at Rp.0 - Rp. 1 Billion. And for the category e-tender highest in the B2 qualification with the contractor’s ability level, they can participate in projects worth Rp.0 - Rp. 50 billion.